Perancangan Gudang untuk Meminimasi Perpindahan Material Handling dengan Metode Hungarian - Farida (Metode : Jurnal Teknik Industri, 2024)
Every year PT X experiences an increase in drug production, causing insufficient raw material warehouse capacity needs. From observation result and analysis, obstacle was found because there were problems in structuring storage of raw materials that were not appropriate. In actual conditions, raw material storage uses block stocking method, but manager plans change storage method to racking method. If after racking method is implemented and turns out capacity is still insufficient, company plans to create an additional warehouse. Focus of this research begins with determining dimensions of  rack then arranging rack in the warehouse, then determining size of warehouse capacity with racking method. Racking method is also used to propose additional warehouse capacity and propose models for raw material allocation. From results of the analysis, proposed rack dimensions are 1.2 x 1.2 x 1.2m3 with arrangement of rack in direction of y-axis so that a storage capacity of 166 pallets is obtained. In actual conditions, PT X uses a raw material storage policy with a random storage policy model and the results of this study propose use of shared storage policy by considering frequency of entry and exit raw materials from warehouse. Determination of location of raw materials using a modified Hungarian model with aim function of minimizing total distance required by material handling. This model has been tested using historical company data that matches the function of goal to be achieved and gives the result that minimum distance required for material handling is less than 100,000meters.